الضغوط الاقتصادية وعلاقتها بمستوى الطموح "دراسة ميدانية في مدينة اللاذقية على عينة من طلبة جامعة تشرين كليتي التربية والحقوق" (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
يهدف البحث الحالي إلى معرفة العلاقة بين الضغوط الاقتصادية ومستوى الطموح لدى عينة من طلاب كليتي التربية والحقوق بجامعة تشرين, وتتلخص مشكلة البحث بالسؤال التالي: ما العلاقة بين الضغوط الاقتصادية ومستوى الطموح لدى عينة من طلبة كليتي التربية والحقوق بجامعة تشرين؟ بلغ حجم عينة البحث (236) طالباً وطالبة من طلاب كليتي التربية والحقوق في جامعة تشرين بمدينة اللاذقية وقد تم استخدام مقياس يبين الضغوط الاقتصادية ومقياس يقيس مستوى الطموح للحصول على البيانات من أفراد العينة كما تم استخدام مجموعة من الأساليب الإحصائية(معامل ألفا كرونباخ, واختبار الدلالــــة T-testلقياس الفروق بين المجموعات), وبعد التطبيق خلص البحث للنتائج الآتية: • عدم وجود فروق بين متوسطات إجابات طلاب كلية التربية و متوسطات إجابات طلاب كلية الحقوق على مقياس مستوى الطموح، وكذلك على مقياس الضغوط الاقتصادية.• عدم وجود فروق دالة إحصائيا بين متوسط إجابات طلاب كلية التربية على مقياسي الطموح والضغوط الاقتصادية تبعا لمتغير الجنس.• وجود فروق دالة إحصائيا بين متوسط إجابات طلاب كلية الحقوق على مقياس الضغوط الاقتصادية, وعدم وجودها على مقياس الطموح تبعا لمتغير الجنس. The research aims to study the relation between economic pressures and the ambition level for sample of educational and low students in Tishreen university. The sample of this research consisted of (236) students (male and female) of educational and low students in Tishreenuniversity in Iattakia. A combination of scale used in the research including a scale of the educational pressures and a scale of level of ambition to get statistics from the sample. A combination of statistical methods were used as following: (T test, Alfa test) the research out com revealed the following:  The results indicated no statistically significant differences between the mean scores of the Faculty educational students and low students on a scale of the economic pressures and a scale of level of ambition. The results indicated no statistically significant differences between the mean scores of educational students due to the variables of gender on a scale of the economic pressures and a scale of level of ambition. The results indicated there are statistically significant differences between the mean scores of low students due to the variables of gender on a scale of the economic pressures. But the results indicated there are no statistically significant differences between the mean scores of low students due to the variables of gender on a scale of level of ambition.